COPD, airflow limitation and chronic bronchitis in farmers: a systematic review and meta-analysis. Issue 1 (27th November 2018) - Guillien, Alicia; Soumagne, Thibaud; Dalphin, Jean-Charles; Degano, Bruno
Abstract : Introduction: The current definition of chronic obstructive pulmonary disease (COPD) associates persistent airflow limitation and chronic respiratory symptoms. Agricultural work has been associated with an increased risk of developing COPD, but the prevalence and definition of the disease vary greatly between studies. This meta-analysis aimed to assess the association between agricultural work and COPD using the most widely used definitions of the disease. Methods: Inclusion criteria were: (1) design: cross-sectional or longitudinal, (2) groups: at least one group of farmers and a control group of non-farmers, (3) outcome: prevalence or unadjusted OR of COPD, airflow limitation and/or chronic bronchitis, (4) study subjects: groups of exposed subjects comprising ≥30 individuals and with a mean age ≥40 years and (5) language: English and French language, full-length, original publications in peer-reviewed journals. Results: In total, 22 manuscripts were included in the meta-analysis. Eight studies assessed only the prevalence of airflow limitation, nine assessed only the prevalence of chronic bronchitis and four assessed the prevalence of both these parameters. Only one assessed the prevalence of COPD according to its current definition, and this study also provided the prevalence of airflow limitation. Ten studies showed a positive association between farming exposure and airflow limitation or chronic bronchitis, and 12 showed no association (OR (95% CI)=1.77 (1.50 to 2.08), p<0.001). Cattle, swine, poultry and crop farming were associated with either airflow limitation or chronic bronchitis. Conclusion: Although some features of COPD are associated with some agricultural work, well-designed studies with appropriate diagnostic criteria should be conducted to draw strong conclusions about the relationship between COPD and farming.